2017
DOI: 10.1515/folmed-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Spondylodiscitis - Epidemiology, Clinical Features, Diagnosis and Treatment

Abstract: Spontaneous spondylodiscitis is a rare but serious infectious disease which is a combination of an inflammatory process, involving one or more adjacent vertebral bodies (spondylitis), the intervertebral discs (discitis) and finally - the neighboring neural structures. In most cases the condition is due to a hematogenous infection and can affect all regions of the spinal cord, but it is usually localized in the lumbar area. The most common clinical symptom is a pronounced, constant and increasing nocturnal para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 37 publications
0
14
0
6
Order By: Relevance
“…Die Spondylodiszitis wird als Infektion durch Erreger mit Befall der Bandscheibe und mit unterschiedlichem Ausmaß der angrenzenden Wirbelkörper definiert [1][2][3][4][5]. Die Letalität liegt heute immer noch zwischen 2 und 17 % [1,3,4,[6][7][8]. Insgesamt ist die Spondylodiszitis mit einer Inzidenz von 1:100.000 Bewohnern/ Jahr eine seltene Erkrankung [6,[9][10][11].…”
Section: Hintergrund Und Fragestellungunclassified
“…Die Spondylodiszitis wird als Infektion durch Erreger mit Befall der Bandscheibe und mit unterschiedlichem Ausmaß der angrenzenden Wirbelkörper definiert [1][2][3][4][5]. Die Letalität liegt heute immer noch zwischen 2 und 17 % [1,3,4,[6][7][8]. Insgesamt ist die Spondylodiszitis mit einer Inzidenz von 1:100.000 Bewohnern/ Jahr eine seltene Erkrankung [6,[9][10][11].…”
Section: Hintergrund Und Fragestellungunclassified
“…Aneta, et al reported neurological symptoms in 1/3 of the cases and ranged from radicular pain to radicu lopathy (29%) to paresis (2-13%) and cauda equina syndrome. (10%) [48]. Current systematic review demonstrated radicular pain and absence of motor deficit in 32% of patients with neurologic findings.…”
Section: Discussionmentioning
confidence: 86%
“…The infection spreads from the disc space into any available space which explains the frequency of epidural abscess formation in the patients with spondylodiscitis. Another important consequence of the delay in diagnosis of spondylodiscitis is the progresson of bony destruction that leads to progressive destruction of the endplates, the trabecular bone of the vertebra and progressive collapse and segmental kyphosis leading to instability [47,48].…”
Section: ) Cord Level Involvementmentioning
confidence: 99%